The World Bank Research Observer 16(2) - World Bank (Cary, NC: Oxford University Press and the World Bank, 2013)
Counting the world's poor: problems and possible solutions; by Angus Deaton. Comments on "counting the world's poor"; by Martin Ravallion, and T. N. Srinivasan. Ecology, history, and development : a perspective from rural Southeast Asia; by Yujiro Hayami. Productivity growth and sustainability in post-green revolution agriculture: the case of the Indian and Pakistan Punjab; by Rinku Murgai, Mubarik Ali, and Derek Byerlee. The politics of Russian enterprise reform: insiders, local governments, and the obstacles to restructuring; by Raj M. Desai and Itzhak Goldberg.